Using integrated hydrological–hydraulic modelling and global data sources to analyse the February 2023 floods in the Umbeluzi Catchment (Mozambique) - Cea, Luis; Álvarez, Manuel; Puertas, Jerónimo (Natural hazards and earth system sciences, 2024)
On 9–13 February 2023 an intense flood event took place in the province of Maputo (Mozambique), resulting in severe damage to agricultural lands and transport infrastructure and with serious consequences for the population. In the district of Boane, located a few kilometres downstream of the Pequenos Libombos dam, the flood destroyed many food crops as well as two bridges linking the district to Maputo, thus affecting the food security of the population. These events are quite frequent in this region, making the delineation of improved flood hazard maps and the development of new flood risk management plans necessary. We reproduce this flood event with a high-resolution integrated hydrologic–hydraulic model fed with freely available global data sources, using a methodology that can be easily reproduced in other data-scarce regions. The model results are validated with observed estimations of the inflow to the Pequenos Libombos reservoir, with water marks left by the flood in the district of Boane, and with a Sentinel-1 image taken during the recession of the flood. We analyse the effect of the Pequenos Libombos reservoir on the flood hazard, which was subject to debate among the affected population and in the media. The results obtained show that integrated hydrologic–hydraulic models based on two-dimensional shallow-water equations, combined with global databases, are currently able to reasonably reproduce the extent and peak discharge of extreme flood events in data-scarce basins and are therefore very useful tools for the development of flood management plans in these regions.